2014
DOI: 10.1371/journal.pone.0099995
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Biofilm Activity: A Function of Klebsiella pneumoniae Capsular Polysaccharide

Abstract: Competition and cooperation phenomena occur within highly interactive biofilm communities and several non-biocides molecules produced by microorganisms have been described as impairing biofilm formation. In this study, we investigated the anti-biofilm capacities of an ubiquitous and biofilm producing bacterium, Klebsiella pneumoniae. Cell-free supernatant from K. pneumoniae planktonic cultures showed anti-biofilm effects on most Gram positive bacteria tested but also encompassed some Gram negative bacilli. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 49 publications
2
26
0
Order By: Relevance
“…However, the extract was found to be ineffective in degrading biofilm since it showed no effect on already formed biofilm of E. coli. Capsular polysaccharides of Klebsiella Pneumoniae, also exhibited nonbiocidal antibiofilm activity by modifying the initial bacteria-surface interactions rather than disrupting the bacterial interactions [15]. Similar results were found where bioactive compound can produce anti-adherence effects between microorganisms and surfaces [16,33].…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…However, the extract was found to be ineffective in degrading biofilm since it showed no effect on already formed biofilm of E. coli. Capsular polysaccharides of Klebsiella Pneumoniae, also exhibited nonbiocidal antibiofilm activity by modifying the initial bacteria-surface interactions rather than disrupting the bacterial interactions [15]. Similar results were found where bioactive compound can produce anti-adherence effects between microorganisms and surfaces [16,33].…”
Section: Discussionsupporting
confidence: 60%
“…Although currently a lot of research is going on for isolation of antibiofilm compounds involving many natural compounds ranging from plant extracts to bacterial metabolites, the focus is mainly on preventing the initial adhesion of bacteria to a surface or lowering the force of adhesion between bacteria and a surface to facilitate removal [13]. Several anti-adhesion strategies have been proposed, including the development of receptor blocks, pre-conditioning of the surfaces with biosurfactants, enzymes, polysaccharides or other bioactive compounds or alteration of the physicochemical properties of the outermost layer of biofilm forming cells for interfering cell-to-surface and/or cell-to-cell communication [14][15][16][17][18][19]. Such approaches might be able to disarm the pathogenic biofilm forming bacteria, establishing "evolution-proof" solution with no selection for resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Although extracellular polysaccharides are essential for the construction of biofilms and are major components of biofilm EPM, numerous reports have shown that some polysaccharides are able to inhibit biofilm formation by many types of microorganisms, including bacteria and fungi (Bendaoud et al 2011;Bernal & Llamas 2012;Rendueles et al 2013;Goncalves et al 2014). In this study, the biofilm formation abilities of diverse bacterial species were compared in the presence of extracellular polysaccharides known to be essential components for biofilm formation, ie LPS and LTA.…”
Section: Discussionmentioning
confidence: 99%
“…• Secretion of 'gelatinous' exopolysaccharides, extra cellular DNA, and proteins to allow formation (Goncalves et al, 2014;Kostakioti et al, 2013;Thurlow et al, 2011). This protects bacteria from antibiotic, immune responses, and shear forces as biofilm matures (Kostakioti et al, 2013) those of antibiotics used to treat biofilms in CF-affected lungs, for example, tobramycin.…”
Section: Biofilm-dispersing Agentsmentioning
confidence: 99%
“…In the US, about 65-80% of nosocomial infections are a result of biofilms (Reffuveille et al 2014;Siala et al 2014) formed by diverse bacteria, for example, Staphylococcus epidermidis, Staphylococcus aureus, Pseudomonas aeruginosa, Escherichia coli and Klebsiella pneumoniae (Burton et al 2006). Biofilms reside in diverse environments in vivo, including plastics, metals, physiological fluids, tissues and bones (Goncalves et al 2014). Sites of biofilm infections that are especially problematic include the lungs of cystic fibrosis (CF) patients (Pompilio et al 2011), diabetic ulcers and medical devices such as catheters (Trautner and Darouiche 2004).…”
Section: Introductionmentioning
confidence: 99%